2000
DOI: 10.1086/315264
|View full text |Cite
|
Sign up to set email alerts
|

Persistence Rate and Progression of Vertically Acquired Hepatitis C Infection

Abstract: Data were collected from 104 infected children who were followed up from birth for a mean of 49 (range, 6-153) months in 22 European centers, to outline the natural history of perinatal hepatitis C virus (HCV) infection. Fifty-four children were persistently HCV RNA positive, 44 were occasionally positive, and 6 never had detectable viremia. At least 90% of the children had evidence of ongoing infection at the latest analysis. Eighteen children became HCV RNA negative at their last assessments, but 40% of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
79
1
6

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(94 citation statements)
references
References 27 publications
8
79
1
6
Order By: Relevance
“…For those patients, mean progression is 0.049 FPR units, corresponding approximately to an increase of 2 Ishak points in 40 years, similarly to other reports. 25,26 Additionally, male gender and HCV genotype 3 resulted in being significantly associated with fast progression, compared to female gender and HCV genotype 1, respectively. Although there is general agreement on the faster disease observed in males, the role of HCV genotype has remained controversial for a long time.…”
Section: Discussionmentioning
confidence: 99%
“…For those patients, mean progression is 0.049 FPR units, corresponding approximately to an increase of 2 Ishak points in 40 years, similarly to other reports. 25,26 Additionally, male gender and HCV genotype 3 resulted in being significantly associated with fast progression, compared to female gender and HCV genotype 1, respectively. Although there is general agreement on the faster disease observed in males, the role of HCV genotype has remained controversial for a long time.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria for the diagnosis of HCV infection have been reported in ref. 6. Physical examination and laboratory testing were usually done every 3-6 months during the first 2 years of life and then every 6 -12 months.…”
Section: Methodsmentioning
confidence: 99%
“…Age and mode of infection are assumed to influence the progression of HCV disease in adults, but limited data are available on the natural history of perinatally acquired HCV infection (4,5). Recent studies suggest that 80% of these children develop chronic infection (6)(7)(8), a rate similar to that documented in adults (9) but higher than that reported in children with posttransfusion HCV infection (10). Persistent HCV infection in infants and children is associated with minimal or mild liver damage and very rarely with advanced liver disease (5,(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…These observations are consistent with those of Resti et al, 21 who concluded that high ALT levels during the first year of life are associated with a higher probability of HCV clearance, even though ALT levels are not a predictive factor for the patient's outcome. Data from the literature show that the viral clearance rate in children is about 15 -20%, with the remaining 80% staying chronically infected, 6,22,23 which is similar to adults. 5 Thus the age at acquisition of infection may not be a relevant factor for the persistence of HCV.…”
Section: Long-term Follow-up Of Children With Vertically Acquired Hcvmentioning
confidence: 96%